Not such silly sausages: Evidence suggests northern quolls exhibit aversion to toads after training with toad sausages. (13th March 2018) - Indigo, Naomi; Smith, James; Webb, Jonathan K.; Phillips, Ben
Abstract: The invasion of toxic cane toads ( Rhinella marina ) is a major threat to northern quolls ( Dasyurus hallucatus ) which are poisoned when they attack this novel prey item. Quolls are now endangered as a consequence of the toad invasion. Conditioned taste aversion can be used to train individual quolls to avoid toads, but we currently lack a training technique that can be used at a landscape scale to buffer entire populations from toad impact. Broad‐scale deployment requires a bait that can be used for training, but there is no guarantee that such a bait will ultimately elicit aversion to toads. Here, we test a manufactured bait – a 'toad sausage' – in a small captive trial, for its ability to elicit aversion to toads in northern quolls. To do this, we exposed one group of quolls to a toad sausage and another to a control sausage and compared the quolls' predatory responses when presented with a dead adult toad. Captive quolls that consumed a single toad sausage showed a reduced interest in cane toads, interacting with them for less than half the time of their untrained counterparts and showing reduced Attack behaviour. We also quantified bait uptake in the field, by both quolls and non‐target species. These field trials showed that wild quolls were the most frequent species attracted to the baits, and that approx. 61% of quolls consumed toad‐aversion baits when first encountered. Between 40% and 68% of these animals developed aversion to further bait consumption. Our results suggest that toad‐aversion sausages may be used to train wild quolls to avoid cane toads. This opens the possibility for broad‐scale quoll training with toad aversion sausages: a technique that may allow wildlife managers to prevent quoll extinctions at a landscape scale.